Sistem Informasi Ekspedisi Barang Pada PT. New Power Global Energy Dengan Menggunakan Metode Extreme Programming - John Roni Coyanda; Nining Ariati; Hastha Sunardi; K.Ghazali K.Ghazali (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
PT New Power Global Energy (NPGE) is a company engaged in freight forwarding services. In its businessprocess, New Power Global Energy is not utilizing technology. To manage all information on shipping goods, an information delivery system is needed so that information is easily understood and traced. The system that is built is The Extreme Programming method is a model that is included in the agile approach introduced by Kent Back. According to his explanation, the definition of XP is as follows: